Assessing translocation effects on an African elephant (Loxodonta africana) source population: demographics, landscape use and response to drones in Majete Wildlife Reserve, Malawi. - Hartmann, Wesley Laurence (2020)
Thesis (MScConsEcol)--Stellenbosch University, 2020.